Faktor Ibu (Inisiasi Menyusu Dini, ASI Eksklusif dan Usia Ibu Melahirkan) Yang Berhubungan Dengan Kejadian Stunting Pada Balita (Systematic Review) - Desi Nurfita; Indah Sari Tanjung; Siti Kurnia Widi Hastuti; Titim Martini; Irawan, Galuh Chandra (Institut Kesehatan Immanuel, 2023)
Stunting is a growth and development disorder experienced by children if their height is below the median length based on height for age to exceed -2 SD of WHO standards. The impact of stunting is not only felt by individuals who experience it but also has an impact on the economy and nation-building. This study aims to examine maternal factors associated with stunting, namely early initiation of breastfeeding, exclusive breastfeeding, and maternal age in children under five in Indonesia. The method used in this systematic review is meta synthesis with a meta aggregation. There is a significant relationship between initiation early breastfeeding and the incidence of stunting in children under five (p = 0.043, p = 0.006, p = 0.000, p = 0.014, p = 0.000, p = 0.033, p = 0.000), there was no relationship between BMI and the incidence of stunting (p = 0.053, p = 0.930). There is a relationship between exclusive breastfeeding and the incidence of stunting (p = 0.000, p = 0.028, p = 0.003, p = 0.001, p = 0.002, p = 0.011, p = 0.033, p = 0.021), there is no significant relationship between exclusive breastfeeding and the incidence of stunting in children under five (p = 0.985, p = 0.327, p = 0.17). There is a relationship between maternal age and the incidence of underfive stunting (p = 0.001). There was no relationship between maternal age and the incidence of stunting among children under five (p = 0.304, p = 0.438). Journals showed a relationship between early initiation of breastfeeding and the incidence of stunting in children under five in Indonesia, 15 journals showed that there was a relationship between exclusive breastfeeding and the incidence of stunting in children under five and only 1 journal showed a relationship between maternal age and the incidence of stunting in children under five.